2017
DOI: 10.1111/1751-2980.12505
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of patients with resectable pancreatic acinar cell carcinoma

Abstract: Compared with ductal adenocarcinoma, resectable pancreatic ACC has a favorable prognosis after surgery. Considering that distant metastasis is the most common pattern of recurrence, further studies are necessary to define the role of adjuvant chemotherapy for improving survival outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 28 publications
3
21
0
Order By: Relevance
“…Interesting, it was shown that patients who were recommended to receive surgery but did not receive operation finally still had favorable prognosis compared with those who had not receive surgical treatment due to the late stages of diseases, showing that apart from surgery, the clinical characteristics themselves had great impact on prognosis of patients with ACC. What is more, similar to other studies 8 , 29 , tumor size was proved not to be an independent prognostic factor for patients with ACC who were more frequently to have large tumors. In addition, there were no significant differences in OS and CSS stratified by tumor size in the present study.…”
Section: Discussionsupporting
confidence: 85%
“…Interesting, it was shown that patients who were recommended to receive surgery but did not receive operation finally still had favorable prognosis compared with those who had not receive surgical treatment due to the late stages of diseases, showing that apart from surgery, the clinical characteristics themselves had great impact on prognosis of patients with ACC. What is more, similar to other studies 8 , 29 , tumor size was proved not to be an independent prognostic factor for patients with ACC who were more frequently to have large tumors. In addition, there were no significant differences in OS and CSS stratified by tumor size in the present study.…”
Section: Discussionsupporting
confidence: 85%
“…Although tumor grade is considered an important prognostic factor for adenocarcinoma [27], we did not find a significant effect of histological grade on OS in patients with ACC (p>0.05). Similar to other studies [12,13,28], tumor size had no significant effect on OS even though ACC unusually presents with larger tumors.…”
Section: Married Patients Had a Better Prognosissupporting
confidence: 86%
“…Although there was a significant improvement in OS in patients undergoing surgery at any stage, the postoperative recurrence rate is as high as 42-72% [8]. Furthermore, the most common pattern of recurrence in ACC is distant metastasis [28], hence the necessity to adopt more active adjuvant therapy strategies after the operation.…”
Section: More Radical Management Methods May Achieve Longer Survivalmentioning
confidence: 99%
“…Due to its rarity, there is no standard treatment for PACC. Complete resection is always the preferred option ( 11 ), and chemotherapy often refers to the regimens of colorectal cancer or ductal adenocarcinoma based on their similar genetic changes for those who cannot undergo resection ( 12 ). A retrospective study showed that about 50%–60% patients diagnosed with metastatic PACC responded to a possible combination of gemcitabine, docetaxel, and erlotinib ( 13 ).…”
Section: Discussionmentioning
confidence: 99%